Natural Killer Cell Recruitment to the Lung During Influenza A Virus Infection Is Dependent on CXCR3, CCR5, and Virus Exposure Dose - Carlin, Lindsey E.; Hemann, Emily A.; Zacharias, Zeb R.; Heusel, Jonathan W.; Legge, Kevin L. (Frontiers in Immunology, 2018)
Natural Killer (NK) cells are vital components of the antiviral immune response, but their contributions in defense against influenza A virus (IAV) are not well understood. To better understand NK cell responses during IAV infections, we examined the magnitude, kinetics, and contribution of NK cells to immunity and protection during high- and low-dose IAV infections. Herein, we demonstrate an increased accumulation of NK cells in the lung in high-dose versus low-dose infections. In part, this increase is due to local proliferation of pulmonary NK cells. However, the majority of NK cell accumulation within the lungs and airways during an IAV infection is due to recruitment that is partially dependent upon CXCR3 and CCR5, respectively. Therefore altogether, our results demonstrate that NK cells are actively recruited to the lungs and airways during IAV infection and that the magnitude of the recruitment may relate to the inflammatory environment found within the tissues during high- and low-dose IAV infections.